Effect of Cryohemolyzed Human Cord Blood-Derived Low Molecular Fraction on Recovery of Morphological Properties and Metabolism of ATP and 2,3-DPG of Human Donor Blood Erythrocytes Under Hypothermic Storage - Zharkova, Evhenia E.; Gulevsky, Oleksandr K. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(2): 157